Subjective trust evaluation model based on membership cloud theory - HUANG Hai-sheng1; WANG Ru-chuan1 (Tongxin xuebao)
According to the characteristics of subjectivity,fuzziness and randomicity in subjective trust,the model of trust evaluation based on membership cloud theory was proposed by introducing the theory of membership cloud. The trust cloud and trust grade cloud were described quantificationally,the process of calculation,synthesis and comprehen-sive operation for the trust evaluation cloud was presented,and the evaluation of trust grade was also presented. The re-sults of experiments show that the trust evaluation model proposed is valid.